Coverage and adequacy of ferrous sulfate supplementation in the prevention of anemia among children treated at health centers of Florianopolis, Santa Catarina - Francieli Cembranel; Arlete Catarina T. Corso; David Alejandro González-Chica (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE To evaluate the National Program of Iron Supplementation (PNSF) coverage, the compliance with the directions for of using of this supplementation and the association with sociodemographic factors in children aged six to 18 months old and registered in 35 public health centers of Florinópolis (Southern Brazil). METHODS Cross-sectional study using secondary data obtained from the health information system of the Health Department of Florianópolis, Santa Catarina, Brazil (Infosaúde). Data on ferrous sulfate supplementation and sociodemographic variables were obtained of all children registered in PNSF in Florianópolis in 2010. STATA 11.0 software was used in the analyses. RESULTS The PNSF covered 6.3% (95%CI 5.9-6.7) of the children; the compliance with the directions regarding age at the onset of supplementation and its frequency was adequate only in 2.4% of the cases (95%CI 1.5-3.7). There was no association with the child's gender, maternal education level and ethnicity or the distance from home to the health center. CONCLUSIONS This study showed low coverage and inadequate compliance with the PNSF directions. Measures to improve this strategy are urgent.